ANALISIS ALIRAN UDARA PADA PIPA KOMPOR BURNER - Irvan Septyan Mulyana (Jurnal Teknik dan Science, 2024)
A used oil burner stove is a type of stove that uses used oil as fuel to produce fire and heat which is used in the cooking process. This concept is more commonly found in areas with limited access to conventional energy sources such as electricity or gas. Apart from that, there is a blower which has an important function to maintain sufficient and high-speed air flow towards the combustion axis, thereby helping to increase oil burning efficiency. This test was carried out using Solidworks software with the CFD or Computational Fluid Dynamic feature which has the function of analyzing fluid flow on an object by entering the required parameters. In this paper, a burner stove pipe with an initial cross-sectional area of 2" inches and a final cross-sectional area of 1/2" inches is used where an initial velocity input is given with independent variables of 2 m/s, 4 m/s and 6 m/s and the output is obtained or The results on the stove burner pipe were 17.9 m/s, 37.3 m/s and 54.6 m/s.